Athletes' Feelings of Isolation and Separateness as Determined by Campus Design: A Theoretical Perspective - Lubker, John R. (My University, 2006)
Many college student-athletes feel isolated from social activities on campus and their social experiences at the university are predominately with other athletes (Pinkerton, Hinz, and Barrow, 1989). Also, student-athletes often rely on their athletic department to solve their problems and provide support, which may lead them to ignore other available services on campus (Ferrante & Etzel, 1991). When hypothesizing about student-athlete isolation it is equally important to examine the impact of environmental determinates on this behavior. The topography of the land and campus design influenced the expansion of most college campuses. Therefore, physical isolation allows the athletic department to operate somewhat free of other departments. It can keep athletes in-house, not having to rely on other campus service providers, which may impact athletes' use of counseling and support services if not offered in or near athletic departments. Presented was a new theoretical perspective on how campus design may affect student-athletes' feelings of isolation and impact service use, and the author proposed interventions and research specific to this theory.
Keywords: isolation; college experience; theory; relationship with campus